2021
DOI: 10.1021/acsearthspacechem.1c00165
|View full text |Cite
|
Sign up to set email alerts
|

Competing Photochemical Effects in Aqueous Carbonyl/Ammonium Brown Carbon Systems

Abstract: Carbonyl-containing volatile organic compounds (CVOCs) have been identified in a variety of atmospherically relevant aqueous aerosol conditions and can contribute significantly to total secondary organic aerosol mass. While dark chemistry has been extensively studied for several CVOC-containing reaction systems, the chemistry of these same compounds under irradiated conditions is not as well understood. We present time-resolved UV− visible measurements and inferred kinetic rate constants for CVOC/ ammonium sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
(203 reference statements)
0
13
0
Order By: Relevance
“…3, 4, and 5 in Table 1) because IM is the most abundant species in the reaction of reduced nitrogen species with glyoxal. 13,17,21 IM concentration was found to be 1 and 3 orders of magnitude higher than IC and BI concentration, respectively. 13,17 Sharp et al 21 found that mass abundance of IM decreased, whereas IC disappeared after irradiation with broadband wavelength.…”
Section: ■ Materials and Methodsmentioning
confidence: 81%
“…3, 4, and 5 in Table 1) because IM is the most abundant species in the reaction of reduced nitrogen species with glyoxal. 13,17,21 IM concentration was found to be 1 and 3 orders of magnitude higher than IC and BI concentration, respectively. 13,17 Sharp et al 21 found that mass abundance of IM decreased, whereas IC disappeared after irradiation with broadband wavelength.…”
Section: ■ Materials and Methodsmentioning
confidence: 81%
“…Recent work suggests that the source of the climate-warming effect of BrC, its absorption of solar radiation, may also be a significant loss process for BrC. Photodegradation/photobleaching of BrC, for some select cases, has been shown to be significant, resulting in atmospheric lifetimes that may be hours or less. , However, the nuances of this photochemical aging for ambient-derived BrC make the prevalence of photobleaching more case-specific, rather than a completely general effect. BrC from methylglyoxal in ammonium sulfate solution was shown to quickly bleach upon irradiation, declining by over 75% within an hour, briefly increase in absorption, and then slowly decline over a period of 24 h .…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Photodegradation/photobleaching of BrC, for some select cases, has been shown to be significant, resulting in atmospheric lifetimes that may be hours or less. , However, the nuances of this photochemical aging for ambient-derived BrC make the prevalence of photobleaching more case-specific, rather than a completely general effect. BrC from methylglyoxal in ammonium sulfate solution was shown to quickly bleach upon irradiation, declining by over 75% within an hour, briefly increase in absorption, and then slowly decline over a period of 24 h . Larger BrC compounds, identified by higher molecular weight, appear to be more resistant to photobleaching; mixtures of many BrC chromophores can lead to photochemical lifetimes orders of magnitude longer than the individual components. , In this work, we focus on the formation aspect of BrC levels, showing that bulk aerosol composition, accounting for both inorganic and organic content, makes the rate of BrC formation quite variable.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…In this virtual special issue, the aqueous oxidation of the isoprene oxidation product 2-methyltetrol was shown to be a potentially significant source of formic and acetic acids in the atmosphere . The photochemical processing of light-absorbing organic aerosol material or “brown carbon” is another potential source of VOCs, with implications for Earth’s radiative balance. , The formation of secondary organic aerosol (SOA) from the chlorine oxidation of α-pinene was characterized, and SOA material formed from α-pinene and d -limonene was shown to be relatively stable when exposed to gas- or liquid-phase water . The heterogeneous chemistry of oleic acid aerosol, a very well-studied system, was re-examined using an inverse multiphase modeling approach, revealing new mechanistic details …”
Section: Fundamentals Of Atmospheric Chemistrymentioning
confidence: 99%